Succession and Replacement of Bacterial Populations in the Caecum of Egg Laying Hens over Their Whole Life - Vídeňská, Petra; Sedlář, Karel; Lukac, Maja; Faldynová, Marcela; Geržová, Lenka; Čejková, Darina; Šišák, František; Rychlík, Ivan (Public Library of Science, 2014)
In this study we characterised the development of caecal microbiota in egg laying hens over their commercial production lifespan, from the day of hatching until 60 weeks of age. Using pyrosequencing of V3/V4 variable regions of 16S rRNA genes for microbiota characterisation, we were able to define 4 different stages of caecal microbiota development. The first stage lasted for the first week of life and was characterised by a high prevalence of Enterobacteriaceae (phylum Proteobacteria). The second stage lasted from week 2 to week 4 and was characterised by nearly an absolute dominance of Lachnospiraceae and Ruminococcaceae (both phylum Firmicutes). The third stage lasted from month 2 to month 6 and was characterised by the succession of Firmicutes at the expense of Bacteroidetes. The fourth stage was typical for adult hens in full egg production aged 7 months or more and was characterised by a constant ratio of Bacteroidetes and Firmicutes formed by equal numbers of the representatives of both phyla.

In this study we characterised the development of caecal microbiota in egg laying hens over their commercial production lifespan, from the day of hatching until 60 weeks of age. Using pyrosequencing of V3/V4 variable regions of 16S rRNA genes for microbiota characterisation, we were able to define 4 different stages of caecal microbiota development. The first stage lasted for the first week of life and was characterised by a high prevalence of Enterobacteriaceae (phylum Proteobacteria). The second stage lasted from week 2 to week 4 and was characterised by nearly an absolute dominance of Lachnospiraceae and Ruminococcaceae (both phylum Firmicutes). The third stage lasted from month 2 to month 6 and was characterised by the succession of Firmicutes at the expense of Bacteroidetes. The fourth stage was typical for adult hens in full egg production aged 7 months or more and was characterised by a constant ratio of Bacteroidetes and Firmicutes formed by equal numbers of the representatives of both phyla.
Succession and Replacement of Bacterial Populations in the Caecum of Egg Laying Hens over Their Whole Life
Keywords: metagenomics; chicken microbiota; 16S rRNA; metagenomics; chicken microbiota; 16S rRNA